Growth and accumulation of nutrients of 'Top Gun' watermelon - Cecílio Filho, Arthur Bernardes [UNESP]; Reyes, Sergio Manuel Rugeles; Ancheschi Filho, João Augusto; Schiavon, Aparecido Alecio; Barbosa, José Carlos [UNESP] (UNESP - Universidade Estadual Paulista, 2018)
An experiment was carried out in the city of Itápolis (SP), from October 2007 to January 2008, in a Red-Yellow Distrophic Argissolo (loamy soil), in order to evaluate growth, accumulation and exportation of macro and micro-nutrients in Top Gun hybrid watermelon. The experimental design took place in randomized blocks, having six different treatments corresponding to the sampling stages of plants: elongation of the main branch; presence of tertiary branches; early flowering; fruit with a diameter of 8 cm; fruit with a mass of between 4 and 5kg; and end of the cycle. The accumulation of dry mass was slow up to 35 DAS, increasing from this point on, reaching 1528 g plant-1 at the end of the cycle. The total accumulated dry mass was made up of 11.6% stems, 19.5% leaves, and 68.9% fruit. In terms of nutrient accumulation, this was also slow up to 35 DAS. With fruiting, came an increase in the demand for nutrients with 45 to 59 DAS being the period of greater nutritional demand. The order of decreasing nutrients was: K> N> Ca> Mg> P> S> Mn> Fe> B> Zn> Cu. The export of macronutrients (in kg ha-1) was 36.4; 4.3; 62.7; 5.0; 6.5; and 2.3 for N, P, K, Ca, Mg and S, respectively. For Mn, Fe, B, Zn and Cu, the values exported in g ha-1 were 137.0; 157.7; 120.4; 60.4 and 22.1, respectively.
Keywords: Citrullus lanatus L.; Dry mass; Macronutrients; Micronutrients; Plant nutrition